Microstrip rectangular patch array antenna: article / Zulkifli Maslan - Maslan, Zulkifli (2010)
This paper presents the design of microstrip rectangular patch array antenna with operating frequency at 2.5GHz for WiMAX application. The array of 4x1 microstrip rectangular patch antenna with microstrip line feeding based on quarter-wave impedance matching technique was designed and simulated using CST Microwave Environment software. The performance of the designed antenna was analyzed in term of return loss, VSWR, bandwidth, directivity, radiation pattern and gain. The antenna was then fabricated on the substrate type FR-4 with dielectric constant of 4.9 and thickness of 1.6mm respectively. The antenna was measured in the laboratory using Vector Network Analyzer (VNA) and the results show good agreement with the simulated performances.